Association of Elevated Plasma FGF21 and Activated FGF21 Signaling in Visceral White Adipose Tissue and Improved Insulin Sensitivity in Gestational Diabetes Mellitus Subtype: A Case-Control Study - Wang, Ning; Sun, Bo; Guo, Haonan; Jing, Yingyu; Ruan, Qi; Wang, Mengjun; Mi, Yang; Chen, Huan; Song, Lin; Cui, Wei (Frontiers in Endocrinology, 2021)
Objective: To study the discrepancy of the insulin sensitivity alteration pattern, circulating fibroblast growth factor (FGF21) levels and FGF21 signaling in visceral white adipose tissue (vWAT) of gestational diabetes mellitus (GDM) subtypes. Methods: 26 GDM women with either a predominant of insulin-secretion defect (GDM-dysfunction, n = 9) or insulin-sensitivity defect (GDM-resistance, n = 17) and 13 normal glucose tolerance (NGT) women scheduled for caesarean-section at term were studied. Blood and vWAT samples were collected at delivery. Results: The insulin sensitivity was improved from the 2nd trimester to delivery in the GDM-resistance group. Elevated circulating FGF21 concentration at delivery, increased FGF receptor 1c and decreased klotho beta gene expression, enhanced ERK1/2 phosphorylation, and increased GLUT1, IR-B, PPAR-γ gene expression in vWAT were found in the GDM-resistance group as compared with the NGT group. The circulating FGF21 concentration was negatively correlated with fasting blood glucose (r = -0.574, P < 0.001), and associated with the GDM-resistance group (r = 0.574, P < 0.001) in pregnant women at delivery. However, we observed no insulin sensitivity alteration in GDM-dysfunction and NGT groups during pregnancy. No differences of plasma FGF21 level and FGF21 signaling in vWAT at delivery were found between women in the GDM-dysfunction and the NGT group. Conclusions: Women with GDM heterogeneity exhibited different insulin sensitivity alteration patterns. The improvement of insulin sensitivity may relate to the elevated circulating FGF21 concentration and activated FGF21 signaling in vWAT at delivery in the GDM-resistance group.